Genetic relatedness of methicillin-resistant Staphylococcus pseudintermedius (MRSP) isolated from a dog and the dog owner - Indarjulianto, Soedarmanto; T., Kanbar; H., Ülbegi-Mohyla; M., Hijazin; M., Zschöck (2011)
In the present study four methicillin-resistant staphylococcus pseudintermedius (MRSP) strains isolated from a dog (n = 3) and the anterior nares of the dog owner (n = 1) were investigated by conventional and molecular methods. The species identity of the four S. seudintermedius strains was confirmed by conventional methods, by PCR mediated amplification of S. intermedius/S. pseudintermedius specific segments of thermonuclease encoding gene nuc and by restriction fragment length polymorphism analysis of phosphoacetyltransferase encoding gene pta. Investigation of the four S. pseudintermedius for toxino- genic potential revealed that all four strains were positive for the exfoliative toxin encoding gene siet and the leukotoxin encoding genes lukS, lukF. The oxacillin and penicillin resistance of the four S. pseud- intermedius strains could be determined by cultivation of the strains on oxacillin resistant screening agar base, ChromID MRSA Agar and Brilliance MRSA Agar and by multiplex PCR detecting the resistance genes mecA and blaZ. The genetic relatedness of the strains was studied by macrorestriction analysis of their chromosomal DNA using pulsed field gel electrophoresis (PFGE). According to PFGE all four S. pseudinter- medius strains represent an identical bacterial clone indicating a cross transmission between the dog and the dog owner.